1975
DOI: 10.2307/3278994
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gonadectomy of Host on Parasitemia and Mortality of Mice Infected with Trypanosoma cruzi

Abstract: Male CF1 mice were more susceptible to acute infections of Trypanosoma cruzi than female mice as evidenced by significantly greater maximum mean parasitemia of approximately 8.9 times 10-6 per ml in males as compared to 1.5 times 10-6 per ml in females. Mortality was also greater in males (80 to 90% as compared to 28% in females). Ovariectomy of female mice made them more susceptible than unoperated female of similar age and stock to the Brazil strain of T. cruzi as indicated by maximum mean parasitemia of 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
14
1
4
Order By: Relevance
“…Resistance appears to be directly linked to the presence of female sex hormones, as ovariectomized females are more susceptible to disease (Chapman et al 1975;Santos et al 2007;D'Ambrosio et al 2008). A role for male sex hormones in mediating susceptibility is less clear, as gonadectomized males are reported to have reduced parasite burdens (D'Ambrosio et al 2008) and unaltered parasitemia and mortality (Chapman et al 1975) when compared with gonadally intact males, which likely reflects differences in mouse and parasite strains.…”
Section: American Trypanosomiasismentioning
confidence: 94%
See 1 more Smart Citation
“…Resistance appears to be directly linked to the presence of female sex hormones, as ovariectomized females are more susceptible to disease (Chapman et al 1975;Santos et al 2007;D'Ambrosio et al 2008). A role for male sex hormones in mediating susceptibility is less clear, as gonadectomized males are reported to have reduced parasite burdens (D'Ambrosio et al 2008) and unaltered parasitemia and mortality (Chapman et al 1975) when compared with gonadally intact males, which likely reflects differences in mouse and parasite strains.…”
Section: American Trypanosomiasismentioning
confidence: 94%
“…Although a great deal remains to be understood about the role of the immune system during disease clearance and pathogenesis, research has shown that sex hormones do play a role in its modulation. It is well documented that in experimental infections, male mice and rats are more susceptible to disease than females (Chapman et al 1975;de Souza et al 2001;dos Santos et al 2005;D'Ambrosio et al 2008). In addition, males are clinically more likely to develop severe cardiomyopathies (Basquiera et al 2003) and exhibit abnormal electrocardiograms more often than females (Brabin and Brabin 1992).…”
Section: American Trypanosomiasismentioning
confidence: 94%
“…Although the role of the immune system during disease clearance and pathogenesis is not well understood, studies have shown sex hormones play a role in disease modulation. It is well documented that male mice and rats are more susceptible to disease than females in T. cruzi experimental infection [142][143][144][145]. In addition, males are clinically more likely to develop severe cardiomyopathies [146] and exhibit abnormal electrocardiograms more often than females [147].…”
Section: In Protozoa Infectionsmentioning
confidence: 99%
“…Susceptibility and/or resistance could be directly linked to the presence of female sex hormones, and ovariectomized females are more susceptible to disease [142,145,148]. However, a role for male sex hormones in mediating susceptibility is less clear, and gonadectomized males are reported to have reduced parasite burdens [145] and unaltered parasitemia and mortality [142]. Interestingly, female mice treated with high pharmacological doses of 17β-estradiol increases parasitemia and mortality.…”
Section: In Protozoa Infectionsmentioning
confidence: 99%
See 1 more Smart Citation